2008
DOI: 10.1088/0957-0233/19/2/025302
|View full text |Cite
|
Sign up to set email alerts
|

Fast in-line surface topography metrology enabling stress calculation for solar cell manufacturing for throughput in excess of 2000 wafers per hour

Abstract: We present a novel structured pattern projection tool for stress, and topography measurement of solar cells. The presented tool has expanded (two standard deviations) accuracy and repeatability of 0.5 mm, exceeding current industry requirements (±0.05 mm one standard deviation). Measurements on the R&D system indicate that this technology is capable of performing measurements with a throughput exceeding 2000 wafers per hour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Their readings were tracked using a PC based data acquisition system. For these tests the stochastic pattern was painted directly on the surface of the solar cell and aluminum surface plate (4).…”
Section: Experimental Methods To Quantify Solar Cell Bowingmentioning
confidence: 99%
“…Their readings were tracked using a PC based data acquisition system. For these tests the stochastic pattern was painted directly on the surface of the solar cell and aluminum surface plate (4).…”
Section: Experimental Methods To Quantify Solar Cell Bowingmentioning
confidence: 99%
“…Recently we developed structured light projection based profilometer for rapid characterization of silicon solar cell wafers described in our earlier paper [2], and subsequent advances in its calibration algorithms [3]. In our earlier paper we demonstrated that structured light projection metrology is capable in meeting throughput requirements for solar cell manufacturing [2].…”
Section: Troductiomentioning
confidence: 99%
“…It is possible to use projector to define a light spot on the surface of the sample and to use such spot for investigation of local characteristics of the measured wafer. We demonstrated that the very same hardware as used in profilometer [2], with new modified software application can be used to measure diffused spectrally resolved reflectance. This approach does not only eliminate costly motion stages, but also increases speed of data acquisition.…”
Section: Troductiomentioning
confidence: 99%
See 2 more Smart Citations